Comparative Effectiveness of Benson Relaxation and Mindfulness Breathing on Blood Pressure Reduction in Hypertensive Patients - Saputra, Ardi Dwi; Wisuda, Aris Citra; Putry, Mayang Novyanti; Suraya, Citra; Hamdan, Ichsan Nur; Martilopa, Iis; Budiyono, Arif; Erpina, Eli; Sari, Indah Tirta (Yayasan Rumah Ilmu Professor, 2025)
Hypertension is a major public health problem and one of the leading risk factors for cardiovascular morbidity and mortality worldwide. Non-pharmacological interventions, such as relaxation and breathing techniques, have been widely explored to complement medical treatment in controlling blood pressure. Benson relaxation and mindfulness breathing are two techniques that may effectively reduce stress and blood pressure through physiological and psychological mechanisms. This study aimed to compare the effectiveness of Benson relaxation and mindfulness breathing interventions in reducing blood pressure among hypertensive patients. A quasi-experimental study was conducted at RSUD Sungai Lilin from February to April 2025. A total of 140 hypertensive patients were selected using total sampling and randomly assigned into two intervention groups: Benson relaxation (n = 70) and mindfulness breathing (n = 70). Interventions were administered regularly for four weeks. Blood pressure was measured before and after the intervention using a standardized sphygmomanometer. Data were analyzed using paired and independent t-tests. Both Benson relaxation and mindfulness breathing significantly reduced systolic and diastolic blood pressure in hypertensive patients (p < 0.05). However, the mindfulness breathing group demonstrated a greater mean reduction in both systolic and diastolic blood pressure compared to the Benson relaxation group (p < 0.05). Both interventions are effective in reducing blood pressure, but mindfulness breathing shows superior effectiveness compared to Benson relaxation. These findings suggest that mindfulness breathing can be recommended as a complementary non-pharmacological therapy for hypertension management.